Teaching the foundations of quantum mechanics in secondary school: a proposed conceptual structure - Fanaro, Maria de los Angeles; Otero, Maria Rita; Argelo, Marcelo (Investigações em Ensino de Ciências, 2016)
This paper is part of a doctoral thesis that investigates Basic Quantum Mechanics (QM) teaching in high school. A Conceptual Structure of Reference (CSR) based on the Path Integral Method of Feynman (1965) was rebuilt and a Proposed Conceptual Structure for Teaching (PCST) (Otero, 2006, 2007) the basics of Quantum Mechanics at secondary school was designed, analysed and carried out. This PCST does not follow the historical route and it is complementary to the canonical formalism. The concepts: probability distribution, quantum system, x(t) alternative, amplitude of probability, sum of probability amplitude, action, Planck's constant, and classic-quantum transition were rebuilt with the students. Mathematical formalism was avoided by using simulation software assistance. The Proposed Conceptual Structure for Teaching (PCST) is described and some results from the test carried out by the class group are discussed. This information allows the analysis of the Conceptual Structure Effectively Reconstructed (CSER) to be initiated with the students.